The Renewable Energy Act 2011: a study on renewable energy development in Malaysia - Ghazali, Farahdilah; Ansari, Abdul Haseeb (Global Academic Excellence, 2018)
Energy security and energy threat are worldwide issues as fossil fuels are exhaustible due to the robust development and economic growth. Many countries across the border support the efforts for alternative energy generation to ensure their energy supply. An energy transition from unsustainable fossil fuel sources to renewable energy (RE) has been reflected by the promulgation of various law and policies in numerous regions and the establishment of the International Renewable Energy Agency (IRENA). Malaysia has also taken several measures to accelerate RE development including the enactment of the Renewable Energy Act 2011 (Act 725). This study focuses on the importance of RE in securing energy supply in Malaysia and discusses the implementation of the Renewable Energy Act 2011 in the country. This study adopts a doctrinal approach by analyzing existing RE law in Malaysia.